Mapping Holistic Growth: Developing a Comprehensive Student Development Scale - Zawad Rami, Apoorva Bhan, Prem Vijoy, Mayura Bijale, Vandna Sharma, (European Economic Letters (EEL), 2024)
This paper describes the construction and psychometric testing of a multidimensional student development instrument designed to measure growth in multiple domains. The research was aimed at developing a measurement framework that would allow for the evaluation of cognitive, emotional, social, and ethical development, at developing and validating a scale based on this framework to ensure the scale’s construct validity and internal consistency, as well as at examining the practical use of the scale in educational contexts and at providing guidelines for its use. The scale was constructed in a step-by-step procedure including item construction, factor analysis, and reliability assessment. Validity and reliability coefficients are high, which proves the efficiency of the scale for assessing the student’s all-round development. Teachers also pointed to the scale’s capacity to address the affective and interpersonal domains alongside the cognitive and moral ones. Suggestions for the future are to incorporate the scale into the students’ development programs, to use it for targeted interventions, and to carry out more studies to examine its applicability in various educational settings. This research offers a useful instrument for the improvement of the student’s development and creates the basis for further investigations in the sphere of the comprehensive development of students.